Effectiveness of Role Play in Improving Speaking Skill - Neupane, Binod (Journal of NELTA Gandaki, 2019)
This study was carried out to find out the effectiveness of role play technique in improving speaking skill in English. The population of the study was the grade X students of a public school from Lamjung district. The experimental group was taught through role play while the control class was taught through the traditional grammar based techniques. The total population of this study was 40 students who were enrolled in the academic year 2018/2019. The study was experimental approach. The tools applied in this research were observation sheet and speaking test. After 20 lessons of the teaching, the post-test of speaking was conducted in which the students in both groups were asked to answer. The results showed that there is a significant improvement in speaking skill of experimental group. It can be concluded that role play have significant effect on students’ speaking skill.